2020
DOI: 10.1038/s41598-020-70725-4
|View full text |Cite
|
Sign up to set email alerts
|

High genetic burden of type 2 diabetes can promote the high prevalence of disease: a longitudinal cohort study in Iran

Abstract: Type 2 diabetes (T2D) is emerging as one of the serious public health issues in both developed and developing counties. Here, we surveyed the worldwide population differentiation in T2D-associated variants and assessed the genetic burden of the disease in an ongoing Tehran Cardio-Metabolic Genetic Study (TCGS) cohort represented the Iranian population. We found multiple SNPs that were significantly depleted or enriched in at least one of the five populations of 1,000 Genome Project (African, American, East Asi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Hence, the high genetic burden of T2D across the Iranian population can contribute to the enhanced prevalence of the disease in this population. In line with this nding, they demonstrated a high hazard of T2D development in the genetically high-risk individuals compared to the genetically low-risk individuals in the model adjusted for age, sex, BMI, and other biochemical T2D risk factors [17].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Hence, the high genetic burden of T2D across the Iranian population can contribute to the enhanced prevalence of the disease in this population. In line with this nding, they demonstrated a high hazard of T2D development in the genetically high-risk individuals compared to the genetically low-risk individuals in the model adjusted for age, sex, BMI, and other biochemical T2D risk factors [17].…”
Section: Resultssupporting
confidence: 67%
“…Complex segregation analysis revealed that the polygenic model well illustrated the mode of inheritance of T2D among the TLGS participants. As a rst step toward the prediction of T2D development using the person-speci c genetic pro le, Moazzam-Jazi et al in 2020 recognized multiple T2D-associated SNPs signi cantly enriched in the TCGS cohort, compared to the global population [17].…”
Section: Resultsmentioning
confidence: 99%
“…Such multiple genetic variants used to build PRS can differ in allele frequencies across populations due to reasons such as natural selection and population expansion leading to adaptation to local environmental factors. A recent study from Iran [30] found multiple T2D-risk SNPs that were significantly depleted or enriched in at least one of the five populations of the 1000 Genome Project (African, American, East Asian, European, and South Asian) as well as the Iranian population. They further found that a PRS built using the enriched risk alleles in Iran was significantly associated with type 2 diabetes incidence in their longitudinal cohort study.…”
Section: Generalizability Of Gwa-identified Association Signals In Arab Populationsmentioning
confidence: 99%
“…The risk of developing depression is influenced by lifestyle choices, environment, and genetics 21 . One approach to evaluate the genetic risk, is to convert genetic data from genome wide association studies (GWASs) into polygenic risk scores (PRSs) 22 .…”
Section: Introductionmentioning
confidence: 99%